Mitral valve finite-element modelling from ultrasound data: a pilot study for a new approach to understand mitral function and clinical scenarios - Votta, Emiliano; Caiani, Enrico; Veronesi, Federico; Soncini, Monica; Montevecchi, Franco Maria; Redaelli, Alberto (Philosophical transactions of the Royal Society of London. Series A: Mathematical, physical, and engineering sciences, 2008)
In the current scientific literature, particular attention is dedicated to the study of the mitral valve and to comprehension of the mechanisms that lead to its normal function, as well as those that trigger possible pathological conditions. One of the adopted approaches consists of computational modelling, which allows quantitative analysis of the mechanical behaviour of the valve by means of continuum mechanics theory and numerical techniques. However, none of the currently available models realistically accounts for all of the aspects that characterize the function of the mitral valve. Here, a new computational model of the mitral valve has been developed from in vivo data, as a first step towards the development of patient-specific models for the evaluation of annuloplasty procedures. A structural finite-element model of the mitral valve has been developed to account for all of the main valvular substructures. In particular, it includes the real geometry and the movement of the annulus and papillary muscles, reconstructed from four-dimensional ultrasound data from a healthy human subject, and a realistic description of the complex mechanical properties of mitral tissues. Preliminary simulations allowed mitral valve closure to be realistically mimicked and the role of annulus and papillary muscle dynamics to be quantified.